Genetic polymorphisms in tumour necrosis factor receptors (TNFRSF1A/1B) illustrate differential treatment response to TNFα inhibitors in patients with Crohn’s disease - Ahmad Qasem; Saleh A Naser; Seela Ramesh (BMJ Open Gastroenterology, 2019)
Background﻿Monoclonal antibodies inhibiting tumour necrosis factor-α (TNFα) signalling pathway (anti-TNFα) have been widely used in Crohn’s disease (CD). However, treatment response varies among patients with CD and the clinical outcome is dependent on single nucleotide polymorphisms (SNP) in TNFα receptor superfamily 1A and 1B (TNFRSF1A/1B).MethodsWe tested nine SNPs in TNFα, TNFRSF1A and TNFRSF1B by TaqMan genotyping from peripheral blood samples of 104 subjects. Additionally, we quantified the effects of these SNPs on their corresponding gene expression by RT-PCR and susceptibility to Mycobacterium avium subsp paratuberculosis (MAP) infection by IS900 nested PCR.ResultsFour SNPs (TNFα:rs1800629, TNFRSF1A:rs767455, TNFRSF1B:rs1061624 and TNFRSF1B:rs3397) were over-represented significantly (p<0.05) among patients with CD compared with healthy controls. The TNFRSF1A:rs767455 GG genotype was found in 15/54 patients with CD (28%), while it was only found in 2/50 healthy controls (4%) (OR 9.2, 95% CI 1.98 to 42.83). The TNFRSF1B:rs3397 TT genotype was found in 15/54 patients with CD (28%) compared with (4/50) healthy controls (8%) (OR 4.4, 95% CI 1.36 to 14.14). Furthermore, the SNPs TNFRSF1A:rs767455 and TNFRSF1B:rs3397 were associated with downregulating their corresponding genes significantly (p<0.05). MAP infection was predominantly found among patients with CD in comparison to healthy controls (57% vs 8%, respectively), which was also dependent on the SNPs TNFRSF1A:rs767455 and TNFRSF1B:rs3397. Our SNP haplotype analysis of TNFRSF1A:rs767455 and TNFRSF1B:rs3397 indicates that the G–T haplotype is significantly distributed among patients with CD (46%) and MAP infection susceptibility is also associated with this specific haplotype (31%).ConclusionThe SNPs TNFRSF1A:rs767455 and TNFRSF1B:rs3397, which are known to affect anti-TNFα clinical outcome in CD, were associated with lower corresponding gene expression and higher MAP infection susceptibility.